The Role of LUS (Lung Ultrasound Score) in the Diagnosis and Monitoring of Pneumonia - Wahyuni, Wahyuni; Pandu Wiriansya, Edward; Mustafa, Maulana Saggaf (PT FORMOSA CENDEKIA GLOBAL, 2024)
Pneumonia is an acute lower respiratory tract disease that affects the lung parenchyma, including the alveoli and interstitial tissue. Radiological examination is considered the gold standard in confirming the diagnosis of pneumonia. The curriculum aims to emphasize the role of ultrasound (USG) in the form of Lung Ultrasound Score (LUS) in diagnosing and monitoring pneumonia. LUS examination is simple, easy to use, cost-effective, non-invasive, and reduces radiation exposure. This tool demonstrates high sensitivity and specificity compared to chest X-rays and CT scans of the chest. However, this diagnostic tool is operator-dependent, hence requiring standardized skills and expertise among operators to diagnose pneumonia consistently.